IDENTIFICATION OF MYCOPLASMA GALLISEPTICUM BY POLYMERASE CHAIN REACTION AND CONVENTIONAL DIAGNOSTICS FROM WHITE LEGHORN LAYER FLOCKS - M. Rauf; Z. I. Chaudhary; M. Younus; A. A. Anjum; M. A. Ali; A. N. Ahmad; M. U. R. Khan (Journal of Animal and Plant Sciences, 2013)
Molecular diagnostic technique (PCR) was compared with conventional culture isolation for Mycoplasma gallisepticum (MG) identification from field cases of chronic respiratory disease (CRD). White leghorn laying birds (n=380) suffering from respiratory diseases were screened by in vitro cultivation of MG on selective media. Growth inhibition test (GIT) was carried out by adding known antibodies against MG. DNA extracted from organs of infected birds was amplified by PCR using species specific primers of MG targeting 16SrRNA gene and visualized by agarose gel electrophoresis. Overall 27.6 percent (104/380) samples from field birds were positive for MG conventional cultivation methods. Out of 104 culture positive isolates, 83 (79.8%) were confirmed as MG through GIT with 21.84 (83/380) overall percentage. Percent proportion for MG in organs of infected birds was higher (68.94%) as determined by PCR. Confirmed presence of 185 base pairs DNA band was considered positive for MG. There was a significant difference between results of PCR and conventional isolation technique determined by Chi square test (P<0.0001). Results recorded by PCR were comparatively higher and technique found better for identification of MG. PCR can efficiently be used for early detection of MG in different poultry flocks. An early diagnosis can help to lower economic burden of poultry layer farmers due to this drastic malady
Keywords: Mycoplasma gallisepticum; isolation; antibodies; PCR and 16SrRNA gene